Assessing Latent Effects of Prenatal Cocaine Exposure on Growth and Risk of Cardiometabolic Disease in Late Adolescence: Design and Methods - Sarah E. Messiah; Steven E. Lipshultz; Tracie L. Miller; Veronica H. Accornero; Emmalee S. Bandstra (Hindawi Limited, 2012)
Prenatal cocaine exposure has been linked to neurocognitive and developmental outcomes throughout childhood. The cardiovascular toxicity of cocaine is also markedly increased in pregnancy, but it is unknown whether this toxicity affects anthropometric growth and the development of cardiometabolic disease risk factors in the offspring across the lifespan. During the early 1990s, the Miami Prenatal Cocaine Study enrolled a cohort of 476 African American children (253 cocaine-exposed, 223 non-cocaine-exposed) and their biological mothers at delivery in a prospective, longitudinal study. The MPCS has collected 12 prior waves of multidomain data on over 400 infants and their mothers/alternate caregivers through mid-adolescence and is now embarking on an additional wave of data collection at ages 18-19 years. We describe here the analytical methods for examining the relationship between prenatal cocaine exposure, anthropometric growth, and cardiometabolic disease risk factors in late adolescence in this minority, urban cohort. Findings from this investigation should inform both the fields of substance use and cardiovascular research about subsequent risks of cocaine ingestion during pregnancy in offspring.